Fatigue life evaluation of a composite steel-concrete roadway bridge through the hot-spot stress method considering progressive pavement deterioration. (1st July 2018) - Alencar, Guilherme; de Jesus, Abílio M.P.; Calçada, Rui A.B.; Silva, José Guilherme S. da
Highlights: Transient hot-spot stresses obtained on the basis of modal superposition technique. Fatigue life of a bridge welded detail effectively evaluated for the NSM and the HSM. A fatigue local approach plus vehicle dynamic interaction and pavement deterioration. Influence of global and local structural behavior on fatigue damage clearly captured. Abstract: Steel and composite steel-concrete bridges are subjected to random traffic loads along their life cycle which generate significant dynamic impacts. The road-roughness of asphalt pavements is one of the most important aspects that contributes to the significant increase of the stress amplitudes and hence to serious load-induced fatigue concerns. In this context, welded joints are well known as the weakest points in bridges, since they are prone to stress concentrations leading to initiation of fatigue cracks being in current design codes evaluated using primarily the nominal stress method (NSM). However, a more accurate stress definition, which considers the complexity of the stress field at the welds, becomes necessary mainly in old roadway steel bridges that are often subjected to out-of-plane stresses. In this paper, the hot-spot stress method (HSM) is used to evaluate the fatigue life of a welded joint subjected to distortion induced-fatigue, considering the vehicle speeds and a progressive deterioration model for the road pavement. The welded joint was modelled by solid elements and was integrated with a 3D dynamic bridge model using the sub modelling technique. Besides the importance of considering the bridge-vehicle dynamic interactions with the pavement road-roughness, the dynamic amplification effects on local stresses and the relatively high scatter found in the fatigue lives considering global and local approaches show that a detailed local stress definition is fundamental to evaluate the fatigue performance of existing roadway bridges. The effects of the annual traffic increase rate on the fatigue life are also discussed.